Metabolism of Biotin and Analogues of Biotin by Microorganisms IV. Degradation of Biotin, Oxybiotin, and Desthiobiotin by Lactobacillus casei - Birnbaum, Jerome (1966)
Birnbaum, Jerome (University of Cincinnati, Cincinnati, Ohio), and Herman C. Lichstein. Metabolism of biotin and analogues of biotin by microorganisms. IV. Degradation of biotin, oxybiotin, and desthiobiotin by Lactobacillus casei. J. Bacteriol. 92:925–930. 1966.—Lactobacillus casei degrades biotin when it is present in excess to products not utilizable for growth by L. plantarum or Saccharomyces cerevisiae. Degrading activity was initiated in the early stationary phase and was controlled by the pH of the medium. Nonproliferating cells, grown previously in excess biotin for 40 hr, metabolized oxybiotin and desthiobiotin as well as biotin. Cells grown in low biotin, or in excess biotin for 20 hr, did not degrade either analogue. Oxybiotin was 50% as active as biotin for growth, whereas desthiobiotin acted as a competitive inhibitor. Cells grown in excess biotin for 40 hr, but not 20 hr, overcame the inhibitory effect of desthiobiotin, when subcultured to media containing a normally inhibitory concentration of the analogue. Moreover, the level of desthiobiotin dropped rapidly during the first 4 to 6 hr before growth ensued. The data indicate that growth in excess biotin enables L. casei to degrade desthiobiotin and, thereby, to overcome the inhibitory effect of the analogue.